(untitled) (Asian-Australasian Journal of Food Safety and Security, 2025)
Escherichia coli is a major foodborne pathogen that plays a critical role in the onset of gastrointestinal illnesses, especially hemorrhagic diarrhea. This bacterium is frequently transmitted through contaminated food and water sources. Its impact is particularly concerning in low- and mid-income countries, where inadequate sanitation, restricted access to clean water, and poor food safety standards contribute to its widespread occurrence. This research focused on identifying E. coli strains and analyzing their antibiotic resistance profiles from broiler meat samples collected across different locations in the Mymensingh district between January and July 2020. A total of 100 broiler meat samples were gathered and subjected to standard microbiological techniques for E. coli detection, including selective culturing, Gram staining, latex agglutination, and PCR. The antimicrobial susceptibility of the isolated strains was assessed using the disk diffusion technique. Results showed that E. coli was detected in 49 out of 100 analyzed samples, corresponding to a prevalence rate of 49%. The 95% confidence interval for this estimate ranged from 39.42% to 58.65%, with a P-value of 0.4908. Among these, 7% were identified as the O157:H7 serotype (7/100; 95% CI: 2.86–13.89; P=0.1495), while 42% were non-O157:H7 strains (42/100; 95% CI: 32.80–51.79; P=0.4543). Analysis of the O157:H7 isolates showed complete resistance to erythromycin (100%), with a majority also resistant to amoxicillin (83.33%). However, high sensitivity was observed for ceftriaxone (85.71%), followed by ciprofloxacin (50.00%) and streptomycin (45.24%). Multidrug resistance (MDR) was observed in 48.98% of the E. coli isolates (24/49; 95% CI: 35.58–62.53), which were found to exhibit eight different resistance profiles, including four MDR patterns. The predominant resistance pattern identified among the isolates was AMX-S-TE, observed in 20.41% of cases (10 out of 49 isolates). Additionally, four isolates exhibited resistance to four different antibiotics representing four distinct antimicrobial classes—specifically amoxicillin, tetracycline, erythromycin, and gentamicin (AMX-TET-ER-GEN). The multiple antibiotic resistance (MAR) index among the isolates varied between 0.13 and 0.50. These findings underscore the presence of antibiotic-resistant E. coli in broiler meat, indicating a possible pathway for the transmission of resistance genes to humans via the food chain. Asian Australas. J. Food Saf. Secur. 2025, 9(1), 16-27